Prevalence, Antimicrobial Resistance, and Molecular Typing of Thermophilic Campylobacter Spp. in a Greek Poultry Slaughterhouse - Sakaridis Ioannis (Sciendo, 2019)
Campylobacter species are one of the leading causes of foodborne disease. Poultry is a major reservoir and source of its transmission to humans. The aim of this study was to estimate the prevalence and antimicrobial resistance of Campylobacter spp. isolated from chicken carcasses, the environment, and processing equipment of a poultry slaughterhouse in Greece, to identify the dominant Campylobacter species and to determine if there are clonal relationships among the isolates. Fifty poultry samples and 25 environmental samples were examined using microbial cultures and PCR. Forty-nine of 50 poultry samples (98%) were found to be positive for Campylobacter spp. The environment of the slaughterhouse was also found to be significantly contaminated with Campylobacter spp. Thirty-seven isolates were found to be susceptible to all antimicrobials tested (56.1%) and 29 isolates showed resistance to at least two of the antimicrobials tested (43.9%). We observed 24 different PFGE-types among the 53 isolates with 14 of them isolated only once, while five PFGE-types were represented by two isolates. The remaining 29 isolates were represented by five PFGE-types each consisting of three to 12 isolates. Regarding the relationship of the PFGE types and corresponding resistance profiles, all strains of each PFGE-type shared the same antimicrobial resistance profile. This study reports evidence for Campylobacter spp. cross-contamination among broiler carcasses in a Greek slaughterhouse.